A woman's odyssey : journals, 1976-1992 - Aaker, Linda, 1948- (University of North Texas Press, 1994)
Politics and passion are spiked with humor and searching in this compelling tale of a modern woman's journey to mid-life. From shooting deer in Texas to shooting pictures in the Himalayas, from boyfriends to babies, from hitchhiking alone in Guatemala to traveling with the Clintons on the pre-election Texas bus tour, Aaker observes and analyses her world with unexpected candor and insight.